Access to and use of unauthorised online HIV self-tests by internet-using French-speaking men who have sex with men. Issue 5 (21st March 2012) - Greacen, Tim; Friboulet, David; Fugon, Lionel; Hefez, Serge; Lorente, Nicolas; Spire, Bruno
Abstract : Objectives: Although not authorised in France, HIV self-tests are easily available online. The authors questioned French-speaking internet-using men who have sex with men (MSM) concerning their access to and use of such tests. Methods: Online questionnaire on sex websites and gay and HIV community websites. A multivariate logistic regression for rare events was used to identify factors associated with accessing self-tests. Results: 9169 MSM completed the questionnaire. 2748 (30%) were aware of online self-tests, but only 82 of those aware and not already HIV positive (3.5%) declared having accessed one and only 69 using it. In the multivariate model, living one's sex-life with men in absolute secrecy (odds ratio (OR)=3.90, 95% CI 1.73 to 8.76), knowing of the tests via a sex partner (OR=3.42, CI 1.39 to 8.41) or an internet search engine (OR=2.18, CI 1.26 to 3.74) but not through the general (OR=0.21, CI 0.11 to 0.42) or the gay press (OR=0.34, CI 0.16 to 0.73), having unprotected anal intercourse with a casual partner in the preceding year (OR=1.90, CI 1.17 to 3.06), using self-tests for other diseases (OR=2.66, CI 1.43 to 4.90), using poppers (OR=2.23, CI 1.35 to 3.67) and doping products (OR=3.53, CI 1.55 to 8) in the preceding year, having done a traditional HIV test but not in the preceding year (OR=1.93, CI 1.14 to 3.32), never having had suicidal thoughts (OR=0.54, CI 0.32 to 0.90) and living in the provinces (OR=1.80, CI 1.01 to 3.25) were all independently associated with accessing self-tests. Conclusions: Although readiness to admit use of unauthorised medical products may have influenced results, few MSM aware of the existence of self-tests actually declared having accessed one. Accessing the self-test was independently associated with both living one's sex-life with men in total secrecy and having had unprotected anal intercourse in the last 12 months, indicating that autonomous self-testing may reduce barriers to testing for this vulnerable population.